High-dose-rate brachytherapy (interventional radiotherapy) in lip carcinoma with rigid needles: a simple technique with excellent results - Guinot, Jose Luis; Tortajada, Maria; Santos, Miguels; Chust, Maria; Arribas, Leoncio (Journal of Contemporary Brachytherapy, 2022)
Lip carcinoma has been treated for years with low-dose-rate (LDR) brachytherapy, achieving local control greater than 90%. Comparison between LDR and high-dose-rate (HDR) showed that they are equivalently efficient in local control, but HDR results in fewer complications. Interstitial implant of rigid needles or plastic tubes (interventional radiotherapy) is the current standard. Lip carcinomas are usually exophytic, and rigid parallel needles allow for a better dose distribution with more homogeneity, by adding needles placed outside the tissue to cover protruding lesions. Treatment is administered in 5 days, B.I.D. 4.5-5 Gy × 9 fractions. This pictorial essay illustrates the technique of implanting rigid needles in post-operative cases of early and advanced carcinomas of the lip. This technique is straightforward to learn, and is practical and safe with appropriate training. It should be considered in selected patients with lip carcinoma as the first therapeutic option. Departments with HDR brachytherapy units and experienced in interventional radiotherapy should be offering such treatment, as it greatly benefits patients with lip cancer diagnosis.